STUDY OF NICKEL POWDER SYNTHESIS USING CONSTANT CURRENT ELECTROLYSIS METHOD - Syakieb Alatas, Salsabilah
Nickel powder is one of the nickel derivative products that has various applications such as in high-strength low alloy steel and superalloys, and heterogeneous catalysts in the petrochemical industry. Nickel powder can be synthesized using electrolysis methods, either in acidic or alkaline electrolytes. Electrolysis in alkaline electrolytes can be an alternative to avoid extensive hydrogen evolution in electrolysis with low nickel concentrations. Solutions containing NH4+/NH3 were selected because it can produce high current efficiency and at the same time can maintain the pH of the electrolyte in a certain range. In this study, a study was conducted on the synthesis of nickel powder using the electrolysis method in alkaline electrolytes NH4Cl/NH3 to produce nickel powder with a morphology approaching spherical. A series of electrolysis experiments were carried out in two stages. Phase I experiments were conducted to determine the optimum electrolysis conditions that produce nickel powder with the smallest size and the significance of the influence of electrolysis parameters on the average grain size of the nickel powder produced. The variables varied were the concentration of Ni2+ 2.5 gpl, 5 gpl, and 10 gpl; current density of 5 A/dm2, 10 A/dm2, and 15 A/dm2; electrolyte temperature of 25, 40, and 60 oC; and electrolysis time of 10, 15, and 20 minutes. Phase II experiments were conducted to determine the effect of thiourea additive addition on nickel powder morphology and the effect of nickel concentration on nickel powder morphology and current efficiency. The electrolyte solution was prepared by dissolving NiSO4.6H2O, and AgNO3 (0.5% mol of nickel) into 500 mL of NH4Cl/NH3 buffer solution. The electrolysis experiment was conducted using nickel anode and 316L stainless steel cathode with a fixed current supply. The resulting Ni powder was characterized using particle size analysis (PSA) to determine the average grain size, scanning electron microscope and energydispersive X-ray spectroscopy (SEM-EDS) to determine the morphology of the nickel powder formed. The optimum condition was achieved at an initial Ni2+ concentration of 10 gpl, a current density of 10 A/dm2, a temperature of 40 oC, and an electrolysis time of 15 minutes, which produced nickel powder having an average size of 13.07 ????m. The Ni2+ concentration significantly affected the average grain size of nickel powder (68.21% contribution). Current density, temperature, and time have a significant effect (9.57%, 4.74%, and 14.29% contributions). The addition of thiourea produced nickel powder with a spheroidal/spherical-agglomerated blood cell-like morphology based on ASTM F1877-05. Decreasing the Ni2+ concentration from 12 gpl to 8 gpl caused a decrease in average grain size of nickel powder with the smallest average size being 7.38 ????m. Increasing the Ni2+ concentration from 6 gpl to 10 gpl caused an increase in current efficiency with the highest level of 64.59%.